P306 MORF-057, an oral selective α4β7 integrin inhibitor for Inflammatory Bowel Disease, leads to specific target engagement in a single and multiple ascending dose study in healthy subjects. (27th May 2021) - Ray, A; Cui, D; Lee, D; Mangada, M M; Jones, J; Bain, G; Traber, P G; Vrishabhendra, L H; Krzeski, P W; Vande Casteele, N; Reardon, M M; Stern, T P; et al.
Abstract: Background: MORF-057 is an orally administered small molecule designed to inhibit the α 4 β 7 receptor, addressing an unmet medical need in inflammatory bowel disease (IBD) patients, and avoiding the need for periodic therapeutic infusions and the risk for infusion-related reactions. This study evaluated single (SAD) and multiple ascending doses (MAD) of MORF-057 in healthy volunteers. Methods: This was a randomized, double-blind, placebo-controlled, single and multiple doses, phase 1 study of the safety, pharmacokinetics (PK), and pharmacodynamics (PD) of MORF-057 conducted in a Phase I Unit in the USA. Subjects were randomized 3:1 to MORF-057 or placebo capsules once daily in the SAD cohorts: 25, 50, 100, 150, and 400 mg; or twice daily (BID) in the MAD cohorts: 100 and 200 mg total daily doses (dosed as 50 and 100 mg BID, respectively). In the MAD cohorts, trough PK samples were obtained premorning or pre-evening dose following administration of 50 or 100 mg BID, respectively. Blood samples to assess receptor occupancy (RO) of α 4 β 7 and α 4 β 1 integrins were obtained prior to the first dose and 12 hours after treatment. Results: To date, 51 healthy subjects were dosed; 1 subject withdrew consent on Day 2 for personal reasons. Eleven non-serious adverse events (AEs) were reported; AEs were mild and did not result in discontinuation. Two reversible mild AEs in the 200 mg MAD cohort were possibly related to MORF-057 (macular / maculopapular rash). No safety signals were identified to date. Following dosing, MORF-057 was rapidly absorbed and systemic exposure increased approximately dose-proportionally (Fig.1). Mean α 4 β 7 RO was found to be greater than 95% after each of the three highest single doses (Fig.2). In multiple dosing, mean α 4 β 7 RO was greater than 90% at the lower dose, while the highest dose tested resulted in α 4 β 7 RO saturation at steady state. α 4 β 1 RO was below the limit of quantitation with mean trough values estimated to be <10% at any of the dose levels. Conclusion: Current results demonstrated that single and multiple ascending doses of MORF-057 were well tolerated, with only mild, non-serious AEs reported that did not result in study drug discontinuation. MORF-057 demonstrated a favorable PK profile where target engagement was confirmed and resulted in α4β7 receptor saturation in many subjects receiving higher doses. These results support further investigation of MORF-057 and provide a basis for dose selection phase 2 studies in patients with IBD. (NCT04580745)